2021
DOI: 10.1111/myc.13247
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cryptococcosis and anti‐granulocyte‐macrophage colony‐stimulating factor autoantibodies: An underappreciated association

Abstract: The development of disseminated cryptococcosis has historically occurred in patients living with advanced human immunodeficiency virus or other immunosuppressive conditions affecting T‐cell function. Recently, patients with anti‐cytokine neutralising autoantibodies have been recognised to be at risk for disseminated infections by opportunistic intracellular pathogens, including Cryptococcus species. Herein, we present a previously healthy 26‐year‐old man who was evaluated with disseminated cryptococcosis invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…These infections may be secondary to PAP, the use of steroids, and/or impaired GM-CSF signaling directly compromising alveolar macrophage immunity to these pathogens ( Punatar et al, 2012 ). Since 2013, high titers of IgG (mostly IgG1) auto-Abs neutralizing 10 ng/ml GM-CSF (plasma diluted 1/10) have been found in patients with adult-onset isolated idiopathic disseminated disease mostly due to Cryptococcus spp., almost exclusively Cryptococcus gattii ( Applen Clancey et al, 2019 ; Browne et al, 2012a ; Crum-Cianflone et al, 2017 ; Demir et al, 2018 ; Huynh et al, 2020 ; Kuo et al, 2017 ; Panackal et al, 2017 ; Perrineau et al, 2020 ; Rosen et al, 2013 ; Saijo et al, 2014 ; Stevenson et al, 2019 ; Viola et al, 2021 ), Nocardia spp. ( Rosen et al, 2015 ), or more rarely, Aspergillus spp.…”
Section: Neutralizing Auto-abs Against Gm-csfmentioning
confidence: 99%
“…These infections may be secondary to PAP, the use of steroids, and/or impaired GM-CSF signaling directly compromising alveolar macrophage immunity to these pathogens ( Punatar et al, 2012 ). Since 2013, high titers of IgG (mostly IgG1) auto-Abs neutralizing 10 ng/ml GM-CSF (plasma diluted 1/10) have been found in patients with adult-onset isolated idiopathic disseminated disease mostly due to Cryptococcus spp., almost exclusively Cryptococcus gattii ( Applen Clancey et al, 2019 ; Browne et al, 2012a ; Crum-Cianflone et al, 2017 ; Demir et al, 2018 ; Huynh et al, 2020 ; Kuo et al, 2017 ; Panackal et al, 2017 ; Perrineau et al, 2020 ; Rosen et al, 2013 ; Saijo et al, 2014 ; Stevenson et al, 2019 ; Viola et al, 2021 ), Nocardia spp. ( Rosen et al, 2015 ), or more rarely, Aspergillus spp.…”
Section: Neutralizing Auto-abs Against Gm-csfmentioning
confidence: 99%
“…We also report that granuloma formation is dependent on GM-CSF signaling, as granulomas are absent in Csf2rb -/mouse background infections with either the WT or mar1 mutant strains. These results are expected because GM-CSF plays a significant role in both C. gattii and C. neoformans infections, as individuals with GM-CSF autoantibodies are unusually susceptible to cryptococcal infection (52)(53)(54). Furthermore, previous work in both mycobacterial (24)(25)(26) and cryptococcal infections (17) has demonstrated that GM-CSF signaling is required for granuloma formation, likely due to its requirement for macrophage recruitment to the lung during early stages of infection.…”
Section: Discussionmentioning
confidence: 79%
“…Here, we found that the granulomatous response in this model is dependent on GM-CSF signaling, as granulomatous regions were absent in Csf2rb −/− mouse background infections with either the WT or mar1 Δ mutant strains. These results were expected because GM-CSF plays a significant role in controlling infections due to both Cryptococcus gattii and C. neoformans , as individuals with GM-CSF autoantibodies are unusually susceptible to cryptococcal infection ( 46 48 ). Furthermore, previous work in both mycobacterial ( 24 26 ) and cryptococcal ( 17 ) infections has demonstrated that GM-CSF signaling is required for granuloma formation, likely due to its requirement for macrophage recruitment to the lung during early stages of infection.…”
Section: Discussionmentioning
confidence: 89%